Why some poor women in Bangladesh do not opt for micro-credit? (Journal of the Bangladesh Agricultural University, 2014)
Despite many positive impacts of micro-credit, some studies found that micro-credits are not reaching the extreme poor. This study is designed to find out the major causes why rural women do not join micro-credit programme. The present study conducted case studies on ten dropped out members, three non-NGO/MFI members and five NGO/MFI officials. The important causes for dropout are high interest rate, poor management of loan money by clients, management of default cases by NGO/MFI officials, starting time of repayments of instalment, improper utilisation of loan money, husbands unacceptable interference, lack of training to utilise the money and difficulty in getting large amount of loan. On the other hand, worry of failure to repay the instalment, unwillingness to take loan and husbands opposition are the main reasons for non-membership of micro-credit programmes. Tough membership criteria set by the NGOs/MFIs restricts the access to micro-credit option for many of the poor families. Though some NGOs/MFIs have some programmes to support the ultra poor, the coverage is limited. One important hurdle to overcome is the psychological poverty. There are many poor people who are not motivated to get involved in the process despite many NGOs/MFIs are operating at their doorsteps. Appropriate actions are needed to increase the coverage of the micro-credit programme to fight against poverty. NGOs/MFIs should focus not only on the profit but also on the true achievement in poverty alleviation. DOI: http://dx.doi.org/10.3329/jbau.v11i2.19927 J. Bangladesh Agril. Univ. 11(2): 285-292, 2013